A CONCEPTUAL APPROACH OF ENTERPRENEURSHIP AND INNOVATIVE ENTERPRENEUR S ROLES TO CONTINUAL DEVELOPMENT (A Literary Study) - Mieke - Rahayu (Prosiding International conference on Information Technology and Business (ICITB), 2015)
Principally, if an enterprise is growing and keepsmaking innovations with a well structured pattern, thestrategies to be done will be more focused and surelyreduce the expenses. It means that innovation as acompetitive source can give a positive response tocustomers and certainly to continual enterpreneurship.This framework is based on a continualenterpreneurship typology, and is included indeveloping a social and institutional entrpreneurship. Itmeans that the implementation of theenterpreneusrship approach to reach the social goaland to gain changes connected to markets as well ascontinuing innovation. This framework givesreferences to managers to introduce continualinnovation and to reach continual enterpreneurship inthe continual development.